Effects of nitrogen application rates on antioxidant contents and antioxidative activities in Chinese cabbage (Brassica chinensis L.) - ZHU Wei-feng; LIN Xian-yong; JIN Chong-wei; ZHANG Yong-song; FANG Ping (浙江大学学报. 农业与生命科学版)
A pot experiment was carried out to study the effects of nitrogen application rates (0, 150 and 300 mg N·kg-1 soil) on antioxidant contents and antioxidative activities in two cultivars (Shuzhouqing and Dongfei) of Chinese cabbage (Brassica chinensis L.). Results show that fresh and dry weights of shoots were markedly increased by increasing nitrogen application rate from 0 mg N·kg-1 to 150 mg N·kg-1, and were significantly decreased with further increasing nitrogen application rate. Nitrate contents in leaf and petiole increased with increasing N application rate. Higher nitrate contents were observed in cultivar of Shuzhouqing than that of Dongfei. Highest contents of ascorbic acid, total phenolics, flavonoid, and DPPH (1,1-diphenyl-2-picrylhydrazyl) radical scavenging rate and FRAP (ferric reducing antioxidant power) value were recorded in the control (0 mg N·kg-1). The contents of ascorbic acid, total phenolics and flavonoids and antioxidative activities were markedly decreased by the increases of nitrogen application rate, while GSH was not affected. However, the highest antioxidant accumulation were founded at the application rate of 150 mg N·kg-1 soil. Therefore, the rate of 150 mg N·kg-1 soil might be the optimal nitrogen application rate for production of both high-yield and high-quality vegetable under this experimental condition.